Етнічна належність у генетиці: литовський випадок - Даукшас, Д. (Народна творчість та етнологія, 2011)
It is a wide-spread opinion in the social sciences that ethnicity and ethnic identity are a subjective process by which an individual identifies himself with one or more groups. Meanwhile, genetics and popular knowledge about it facilitate an understanding of ethnicity as having a material basis. This article, using data from fieldwork, analyzes how geneticists use the concept of ethnicity.